2018
DOI: 10.5009/gnl17048
|View full text |Cite
|
Sign up to set email alerts
|

The Real-World Safety and Efficacy of Daclatasvir and Asunaprevir for Elderly Patients

Abstract: Background/AimsAlthough daclatasvir with asunaprevir was approved in Japan for interferon ineligible or intolerant patients, patients aged ≥75 years were excluded in the phase III trial. The present study aimed to evaluate the safety and efficacy of this therapy for elderly patients aged ≥75 years and to clarify whether an extremely high sustained virological response (SVR) rate can be achieved, even in a real-world setting when patients with resistance-associated substitutions (RASs) to nonstructural protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Safety outcomes were reported by 10 studies (1 RCT, 1 SAT and 8 observational studies) . The risk of bias of the included studies is shown in Table and .…”
Section: Resultsmentioning
confidence: 99%
“…Safety outcomes were reported by 10 studies (1 RCT, 1 SAT and 8 observational studies) . The risk of bias of the included studies is shown in Table and .…”
Section: Resultsmentioning
confidence: 99%
“…Testing for pre‐existing NS5A RASs before this therapy was therefore recommended in the Japanese guidelines to avoid treatment failure where possible . In fact, the SVR rate for this therapy among patients without NS5A RASs and failure of simeprevir‐based triple therapy was extremely high (98%) in our prospective cohort study in a real‐world setting …”
Section: Introductionmentioning
confidence: 84%
“…Ursodeoxycholic acid (UDCA) has long been used empirically as a drug for cholestatic drug-induced liver injury to shorten the time to resolution [ 11 , 12 ]. For daclatasvir/asunaprevir as an NS3 protease inhibitor-containing regimen, Taki et al indicated that the lower frequency of serious drug-induced liver injury compared to previous reports may have been attributable to the use of add-on UDCA [ 13 ]. However, evidence for the efficacy of UDCA for protease inhibitor-induced liver injury remains insufficient.…”
Section: Introductionmentioning
confidence: 99%